(untitled) (Journal of Governance and Development (JGD), 2018)
UNDPâ€™s Human Development Report 1994 is perhaps among the earliest documents that recognized human security, a concept which eventually led to its frequent use among scholars and practitioners in the International Relations study. Relevantly, the study of drug trafï¬cking from a human security perspective represents a signiï¬cant shift from the mainstream paradigm which focuses more on state-centric rather than an individual human being. In Malaysia, the drug trafï¬cking issue has been of great concern since the 1970s, not only to the public but also the government. This country has long been in the grasp of drug trafï¬cking phenomena. Despite numerous efforts, prevention programmes, law implementations and regional initiatives in combating this issue, the struggle to eradicate or even minimize the problem has never been achieved fully. Drug trafï¬cking trend in the country has evolved to a much greater phase. The trend now becomes more serious and life-threatening in recent times when human - also known as a drug-mule - are increasingly exploited and used as a tool to transport drugs. The purpose of this paper is to examine the modus operandi of drug trafï¬cking network using â€˜drug muleâ€™ as a transporter of drugs in Malaysia. In contrast to the mainstream state centric-based paradigm in international relations, this issue will be analysed from a human security perspective by utilizing the existing literature, such as books, journals, reports, magazines and newspapers. Preliminary ï¬ndings from the literature suggest that drug trafï¬cking continue to pose a threat to human security. The overarching goals of protecting human security cannot be achieved without the commitments from both the government and the international community.